Structural Basis of Parasitic HSP90 ATPase Inhibition by Small Molecules - Giusy Tassone; Marco Mazzorana; Cecilia Pozzi (MDPI AG, 2022)
Protozoan parasites are responsible for several harmful and widespread human diseases that cause high morbidity and mortality. Currently available treatments have serious limitations due to poor efficiency, strong adverse effects, and high cost. Hence, the identification of new targets and the development of specific drug therapies against parasitic diseases are urgent needs. Heat shock protein 90 (HSP90) is an ATP-dependent molecular chaperone that plays a key role in parasite survival during the various differentiation stages, spread over the vector insect and the human host, which they undergo during their life cycle. The N-terminal domain (NTD) of HSP90, containing the main determinants for ATPase activity, represents the most druggable domain for inhibitor targeting. The molecules investigated on parasite HSP90 are mainly developed from known inhibitors of the human counterpart, and they have strong limitations due to selectivity issues, accounting for the high conservation of the ATP-binding site between the parasite and human proteins. The current review highlights the recent structural progress made to support the rational design of new molecules able to effectively block the chaperone activity of parasite HSP90.